Hubungan Efek Samping Obat Anti Tuberkulosis Dengan Kualitas Hidup Pasien TB Di Puskesmas Banyuglugur Situbondo - Iwan Efendi; Alwin Widhiyanto; Ainul Yaqin Salam (Lembaga Pengembangan Kinerja Dosen, 2023)
Tuberculosis (TB) is a disease that is ranked 10th with the highest number of deaths. Side effects caused by Anti-Tuberculosis Drugs (OAT) are often experienced by TB patients and result in physical disorders that reduce the quality of life of TB patients. This study aims to analyze the relationship between OAT side effects and the quality of life of TB patients at the Banyuglugur Community Health Center The research design in the study used a cross sectional approach. The population of this study was all TB patients in the Banyuglugur health center working area who underwent treatment for <6 months according to the inclusion criteria in January 2022 - May 2023, totaling 40 people using the Total Sampling sampling technique. Data were collected using a questionnaire on OAT side effects and quality of life. The analytical test used was the Spearman Rank test. The results of this study showed that the side effects of OAT in 27 TB patients (67.5%) were severe and the quality of life of 31 TB patients (77.5%) was poor. The results of the analysis show a p value of .001 (smaller than 0.05), so there is a significant linear relationship between the OAT side effect variable and the quality of life of TB patients at the Banyuglugur Community Health Center. This research shows that the side effects experienced by TB sufferers, both mild and severe, greatly affect the quality of life of TB patients. Health workers must always carry out routine monitoring of OAT side effects experienced by TB sufferers and treat them as soon as possible so that they do not affect the quality of life of TB patients in terms of physical, nutritional or psychological aspects in order to prevent them from dropping out of treatment.